094 Query

#$&*

course MTH 277

9/13 9:34

Question: Find v X w when v = sin(theta)i + cos(theta)j and w = -cos(theta)i + sin(theta)j (theta is any angle).YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

v X w = (cos theta)(sin theta)i - (sin theta)(cos theta)j

v X w = [(cos theta)(0) - (0)(sin theta)]i - [(sin theta)(0) - (0)(-cos theta)]j + [(sin theta)(sin theta) - (cos theta)(-cos theta)]k

v X w = ((sin theta)^2)k + ((cos theta)^2)k

v X w = [(sin theta)^2 + (cos theta)^2]k

v X w = k

confidence rating #$&*:8232;

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

The result is just the vector k:

v X w = ( sin(theta) i + cos(theta) j ) X (-cos(theta) i + sin(theta) j )

= -sin(theta) cos(theta) i X i + sin(theta) sin(theta) i X j - cos(theta) cos(theta) j X i + cos(theta) sin(theta) j X j.

i X i amd j X j are both zero, since sin(theta) = 0 for both of these computations.

i X j = k by the right-hand rule, and likewise j X i . = -k, so the product is

sin(theta) sin(theta) k - cos(theta) cos(theta) (-k) = sin^2(theta) i + cos^2(theta) k = (sin^2(theta) + cos^2(theta) ) * k = k

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary): OK

------------------------------------------------

Self-critique rating: OK

*********************************************

Question: Find sin(theta) where theta is the angle between v = -i + j and w = -i + j + 2k.

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

|| v X w || = || v || || w || sin(theta)

v X w = [(1)(2) - (0)(1)]i - [(-1)(2) - (0)(-1)]j + [(-1)(1) - (1)(-1)]k

v X w = (2 - 0)i - (-2 - 0)j + (-1 + 1)k

v X w = 2i + 2j -k

|| v X w || = sqrt [ 2^2 + 2^2 + (-1)^2]

|| v X w || = sqrt [4 + 4 + 1]

|| v X w || = sqrt (6)

|| v || = sqrt [(-1)^2 + 1^2]

|| v || = sqrt [1 + 1]

|| v || = sqrt (2)

|| w || = sqrt [(-1)^2 + 1^2 + 2^2]

|| w || = sqrt [1 + 1 + 4]

|| w || = sqrt (6)

sqrt 6 = (sqrt 2)(sqrt 6) (sin theta)

1/ (sqrt 2) = sin theta

theta = 45 degrees

confidence rating #$&*:

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

|| v X w || = || v || || w || sin(theta) so

sin(theta) = || v X w || / (|| v || || w || ) = || 2 j + 2 i || / (sqrt(2) sqrt(6) ) = 2 sqrt(2) / ( sqrt(2) sqrt(6) ) = 2 / sqrt(6) = 2 sqrt(6) / 6 - sqrt(6) / 3.

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary): OK

------------------------------------------------

Self-critique rating: OK

*********************************************

Question: Find a unit vector which is orthogonal to both v = 2i - j and w = 2j - k.

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

v X w = [(-1)(-1) - (0)(2)]i - [(2)(-1) - (0)(0)]j + [(2)(2) - (-1)(0)]k

v X w = [1 - 0]i - [-2 - 0]j + [4 + 1]k

v X w = i + 2j + 5k

|| v X w || = sqrt [1^2 + 2^2 + 5^2]

|| v X w || = sqrt [1 + 4 + 25]

|| v X w || = sqrt (29)

u = (1 / (sqrt 29)) (i + 2j + 5k)

u = (i / (sqrt 29)) + (2j / (sqrt 29)) + (5k / (sqrt 29))

confidence rating #$&*:

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

v X w is orthogonal to both v and w.

v X w = i + 2 j +4 k

A unit vector in this direction is

(i + 2 j + 4 k ) / sqrt(1^2 + 2^2 + 4^2) = (i + 2 j + 4 k ) sqrt(21) / 21 .

If we take the dot product of this vector with either of our original vectors we will get zero. You can verify that this vector is indeed a unit vector.

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):

Although I did not get the correct solution, I worked through the correct sequence of steps. I messed up in one of the first parts of the problem: v X w = [1 - 0]i - [-2 - 0]j + [4 + 1]k. This equation should read v X w = [1 - 0]i - [-2 - 0]j + [4 + 0]k because (-1)(0) = 0, not -1.

------------------------------------------------

Self-critique rating: 3

*********************************************

Question: Find the area of the triangle with vertices P(2,0,0), Q(1,1,-1), R(3,1,2).

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

PQ = (1 - 2)i + (1 - 0)j + (-1 - 0)k

PQ = -i + j - k

PR = (3 - 2)i + (1 - 0)j + (2 - 0)k

PR = i + j +2k

PQ x PR = [(1)(2) - (-1)(1)]i - [(-1)(2) - (-1)(1)] j + [(-1)(1) - (1)(1)]k

PQ x PR = (2 + 1)i - (-2 + 1)j + (-1 + 1)k

PQ x PR = 3i + j

A = (.5)(|| PQ X PR ||)

A = (.5)(sqrt (3^2 + 1^2))

A = (sqrt 10) / 2

confidence rating #$&*:232;2

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):

------------------------------------------------

Self-critique rating:

*********************************************

Question: Determine if each of the following products is a vector, scalar, or not defined at all. Explain why. u X (v X w) , u dot (v dot w), (u X v) dot (w X r).

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

u X (v X w) = vector

use cab-bac formula: a x (b x c) = (c dot a)b - (b dot a)c

u dot (v dot w) = neither

(u X v) dot (w X r) = neither

*** Unless the equation matches a formula given for a vector in the book, I do not know how to determine whether a product is a vector, a scalar, or neither.

Confidence rating: 1

.............................................

Given Solution:

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):

------------------------------------------------

Self-critique rating:

*********************************************

Question: Find a number t such that the vectors -i - j, i - (1/2) j + (1/2)k and -2i -2j - 2tk all lie in the same plane.

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

(-i - j) x ( i - (1/2)j + (1/2)k) = [(-1)(1/2) - (0)(-1/2)]i - [(-1)(1/2) - (0)(1)] j + [(-1)(-1/2) - (-1)(1)] k

(-1/2)i - (-1/2)j + (3/2)k

((-1/2)i - (-1/2)j + (3/2)k) x (-2i -2j - 2tk) = [(1/2)(-2t) - (3/2)(-2)]i - [(-1/2)(-2t) - (3/2)(2)] j + [(-1/2)(-2) - (1/2)(2)]k

(-t + 3)i - (t - 3)j + (1-1)k

(3 - t)i + (-t + 3)j

0 = sqrt [ (3-t)^2 + (3-t)^2]

0 = sqrt [2 * (3 - t)^2]

0 = (3 - t) (sqrt 2)

0 = 3 - t

t = 3

confidence rating #$&*:

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):

------------------------------------------------

Self-critique rating:"

Self-critique (if necessary):

------------------------------------------------

Self-critique rating:

Self-critique (if necessary):

------------------------------------------------

Self-critique rating:

#*&!

Self-critique (if necessary):

------------------------------------------------

Self-critique rating:

#*&!#*&!

&#Very good work. Let me know if you have questions. &#